2003
DOI: 10.1002/hlca.200390346
|View full text |Cite
|
Sign up to set email alerts
|

On Penicillin‐Binding Protein 1b Affinity‐Labeling Reagents

Abstract: Dedicated to Professor Duilio Arigoni on the occasion of his 75th birthdayThe synthesis of some 3-aryl-3-(trifluoromethyl)3H-diazirine and benzophenone-based photoaffinity labels is reported. The photolabile group is bound to a scaffold that also accommodates functional groups to which an indicator unit (biotin) and the bioactive ligand can be attached orthogonally. To three of the labels, moenomycin was conjugated with the aim to provide tools for the identification of the moenomycin binding site within the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
0
11
0
2
Order By: Relevance
“…The moenomycins interfere with the transglycosylation reaction by inhibition of some membrane-bound, nonpenicillin-binding, monofunctional glycosyltransferases (Mgts) and some class A high-molecular-mass penicillin-binding proteins (HMM-PBPs) [2,3,[7][8][9][10][11][12]. Class A HMM-PBPs, such as the PBP1b from Escherichia coli, are two-domain proteins that catalyze both the transglycosylation reaction and the transpeptidation reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The moenomycins interfere with the transglycosylation reaction by inhibition of some membrane-bound, nonpenicillin-binding, monofunctional glycosyltransferases (Mgts) and some class A high-molecular-mass penicillin-binding proteins (HMM-PBPs) [2,3,[7][8][9][10][11][12]. Class A HMM-PBPs, such as the PBP1b from Escherichia coli, are two-domain proteins that catalyze both the transglycosylation reaction and the transpeptidation reaction.…”
mentioning
confidence: 99%
“…Class A HMM-PBPs, such as the PBP1b from Escherichia coli, are two-domain proteins that catalyze both the transglycosylation reaction and the transpeptidation reaction. While ␤-lactam antibiotics bind covalently to an activesite serine in the transpeptidase domain of this bifunctional enzymes, moenomycins are assumed to act as competitive inhibitors at the transglycosylase domain [3,[7][8][9][10]. Although several antibiotics interfere with the transglycosylation reaction, moenomycins are the only compounds known to date that directly interact with the transglycosylases rather than bind to their substrates [3].…”
mentioning
confidence: 99%
“…the transglycosylation domain of E. coli PBP 1b) are the moenomycin antibiotics. It was found that the binding of moenomycin A ( 1 ) to E. coli PBP 1b is reversible,3 and photoaffinity labeling has recently provided evidence that binding occurs indeed at the transglycosylation domain 7. Moenomycin A ( 1 ) and related antibiotics8 were discovered following extensive industrial screening in the 1960s and 1970s 9.…”
Section: Methodsmentioning
confidence: 99%
“…From the 60s, various substituted diaziridines and diazirines were synthesized [29–43]. Halogen derivatives are ideal precursors for spectroscopic studies of carbens [44–46]; several derivatives were suggested as alkylating agents [47] and potential reagents for photolabeling of biological receptor sites [48–57], some of the substituted diaziridines and diazirines were investigated as anticancer drugs [58, 59], potential monoamine oxidase inhibitors [60, 61] and anesthetics [62, 63]. At the same time, to our astonishment, diazirine and diaziridine derivatives practically are not investigated as chemical means of plant protection [64].…”
Section: Introductionmentioning
confidence: 99%